PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI MASA PANDEMI COVID-19 (Studi Kasus Pada Sub. Perbendaharaan dan Pembiayaan Kementrian Pendidikan dan Kebudayaan) - Riesta Athina Rahma (2021)
This study is a quantitative study that aims to determine the effect of work discipline and work motivation on employee performance. This study uses employees of the Ministry of Education and Culture of the Finance Bureau Sub. Financing and Treasury with a population sample of 50 permanent employees as respondents. And in testing and processing data, researchers use the SmartPLS 3.0 application. The results of the test obtained (1) Work Discipline has a significant positive effect on Employee Performance during the pandemic, and (2) Work Motivation has a significant positive effect on Employee Performance during the pandemic.